Short-Term Analysis (8 Weeks) of Social Distancing and Isolation on Mental Health and Physical Activity Behavior During COVID-19 - Peterson, Jessica Ann; Chesbro, Grant; Larson, Rebecca; Larson, Daniel; Black, Christopher D. (Frontiers in Psychology, 2021)
Due to the COVID-19 pandemic, cities and states adopted social distancing, social isolation, or quarantine measurements to slow the transmission of the disease. Negative mental health outcomes including depression and anxiety have been associated with social distancing or social isolation. The purpose of the present study was to examine changes in psychological health and physical activity over an 8 week period under social distancing policies during the COVID-19 pandemic. Methods: 90 individuals participated in this study. Qualifying participants answered questions using an online survey regarding their loneliness, depression, anxiety, mood state, and physical activity over four time points each lasting two weeks. Results: Symptoms of depression and state anxiety were increased in the population when compared to nationwide statistics from before the COVID-19 pandemic. Time point 2, approximately 1 month into social isolation, showed the most significant effects on mental health. During this time point, 100% of the participants showed symptoms of depression. There were no significant changes in physical activity over the 8 weeks. Loneliness, depression, fatigue, and mood state were negatively associated with participation in physical activity. Vigor and state anxiety were associated with participation in physical activity. Conclusion: Social isolation and social distancing practices have had a negative effect on depression, anxiety, and mood over time. It appeared that depression and total mood disturbance was elevated during time point two. Depressive symptoms were much higher than average compared to previous epidemiological data. Physical activity amount did not change over time but was associated with poor mental health.